Protean Neuroophthalmic Presentations of Common Childhood Malignancies—A Report of Two Cases - Roy, Pritam Singha; Jain, Richa; Bhatia, Anmol; Mallik, Nabhajit; Kumar, Narender (Indian Journal of Medical and Paediatric Oncology, 2023)
Common pediatric malignancies often surprise clinicians with unusual presentations. In this narrative, we report two patients with common childhood cancer having unique neuroophthalmic characteristics. In the first case, we have a child with a common childhood solid tumor presenting with blindness without proptosis, while the second case is of a child with a common hematological malignancy presenting with unilateral proptosis without visual impairment. The report highlights that common childhood cancers may present with neuroophthalmic symptoms on rare occasions, creating a diagnostic conundrum.
Keywords: blindness; leukemia; marrow; neuroblastoma; proptosis